PEMBAYARAN UPAH BURUH PERUSAHAAN YANG PAILIT AKIBAT PANDEMI COVID-19 - Siti Afiyah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
As a result of the Covid_19 Pandemic which resulted in the very decline of the community's economy from the top to the bottom. Workers are one of the parties when a company goes bankrupt, but often in the bankruptcy process the constitutional rights of workers are ignored. Indonesia is a state of law (rechtstaat), not based on power (machtstaat)", meaning that everything done by the State and by all its elements can be legally held accountable. Wage is an income as a reward from the entrepreneur to the worker for a job or service that has been or will be performed, declared or valued in the form of money determined according to an agreement or statutory regulation, and paid on the basis of a work agreement between the entrepreneur and the worker. , including allowances for both the workers themselves and their families. Based on the article of the 1945 Constitution, it is stated that wages must meet a decent living for humanity. Thus, the fulfillment of a decent wage for livelihood and humanity is a wage concept that is constitutionally applicable in Indonesia.